MORPHOLOGY OF FRESH WATER CRAYFISH(Cherax quadricarinatus) - Ganda Aliem Pakarsya Lubis; Rahman Karnila; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT Freshwater crayfish is invertebrate animals belonging to the phylum arthropoda that lives in water. This study aimed to find out about the morfology and proportion of crayfish. The method used in this research is exploratory in which the data was analyzed descriptively. The method of determining the parts of freshwater crayfish is divided into several parts consisting of meat, head, skin and calculated the percentage of freshwater crayfish. The results of calculating the body parts of crayfish showed that the percentage of meat was 46.16%, head 28.00%, skin 19.13% and dirt 6.71%. The highest proportion of freshwater crayfish is meat at 46.16%. Keywords: Freshwater Lobster, Preparation, Proportion.